(untitled) (Journal of Hama University, 2022)
The strengthening of denture’s bases is considered one of the useful solutions for improving the fracture resistance caused by repeated usage or unintentional accidents, Given the prevalence of PMMA and its disadvantages related to mechanical properties, the option of strengthening it by various methods has emerged as an urgent necessity. Aim: This laboratory study aims to compare the flexural and impact resistance of denture’s bases reinforced with E-glass fiber mesh, chromium-cobalt metal mesh and non-reinforced bases. The study sample included 90 acrylic samples in rectangular form and measurements of 60x10x3 mm, Samples were divided into 3 groups, first group consisted of 30 as a control sample without reinforcement, second group consisted of 30 reinforced with a chromium-cobalt mesh, and third group consisted of 30 reinforced with a mesh of E-glass fiber, and were tested by flexural strength, impact resistance. The results of the statistical analysis showed the superiority of the chromium-cobalt supported samples over both the control and the fiber-reinforced samples in flexural strength, while the fiber-reinforced samples were superior to the control and the chrom-cobalt supported samples in impact resistance. Within the limits of this study, it can be concluded that the two reinforcement techniques improved both flexural strength and impact resistance compared to none-reinforced, and the chromium-cobalt reinforcement was superior in terms of resistance to flexural forces, however glass-fiber reinforcement was superior in terms of impact forces